Вербалізація концепту багатство у польській мовній картині світу - Гулеватенко Данило Миколайович (My University, 2024)
Робота присвячена вивченню концепту «багатство» у сучасній польській мовній картині світу та лінгвокультурі. Розглянуто поняття концепту у лінгвістиці. Виокремлено основні методи дослідження концепту. Детально розглянуто поняття «мовна картина світу», як вияв ментальності народу. Особливу увагу приділено фразеології, як способу мовного світобачення. Визначено її предмет та об’єкт. Виділено основні типи та критерії класифікації фразеологізмів. Розглянуто фразеологічні одиниці зі структурою словосполучення та речення у польській мові. Досліджено роль фразеології у польській етнокультурі. Визначено основні характеристики концепту «багатство» у польській мові. Виконано семантичний аналіз польських фразеологічних одиниць, що містять даний концепт у своєму складі. На його підставі з’ясовано особливості змістового наповнення концепту «багатство» у сучасній польській мовній картині світу.

Research work is devoted to the study of the concept of "wealth" in the modern Polish linguistic picture of the world and linguistic culture. The notion of concept in linguistics is considered. The main methods of concept research are highlighted. The concept of "language picture of the world" as a manifestation of the mentality of the people is considered in detail. Special attention is paid to phraseology as a way of linguistic worldview. Its subject and object of the research are defined. The main types and criteria for the classification of phraseological units are highlighted. Phraseological units with the structure of word combinations and sentences in the Polish language are considered. The role of phraseology in Polish ethnoculture is studied. The main characteristics of the concept "wealth" in the Polish language have been determined. Semantic analysis of Polish phraseological units containing this concept in their composition was carried out. On the basisof it , the peculiarities of the content of the concept of "wealth" in the modern Polish linguistic picture of the world have been clarified.
Keywords: концепт; мовна картина світу; фразеологія; фразеологічна одиниця; семантичний аналіз; concept; language picture of the world; phraseology; phraseological unit; semantic analysis